Kromo Tani Melawan: Haji Misbach dan Aksi Protes Kaum Tani Surakarta Tahun 1919 - Muhammad Bagus Saefiyansyah Putra; Andi Suwirta (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2022)
This writing examines the role of Haji Misbach and its relation to the peasant's protest in Surakarta in 1919. Between 1918-1919 Haji Misbach was an active member of NIP (Nationaal Indische Partij), also called Insulinde or Sarekat Hindia, along with Tjipro Mangoenkoesoemo and Soewardi Soerjaningrat. He also represented Nyonya Vogel as a leader of the NIP branch in Surakarta. Haji Misbach as a propagandist of NIP had a significant role in the emergence of peasant protests in Surakarta around May 1919. He organized peasants in Surakarta into the krings, under NIP, based on the villages where the peasants lived. Therefore Misbach's intention in organizing the peasants was to unify them, peasants, to struggle against the oppression from the capitalist and colonial government. He not only organized, but he also reminded it is readers about how essential unity was. Besides, through Islam Bergerak, toward the peasant's protest in Surakarta, it published a caricature that clearly illustrates the power relation between the capitalist to the oppressed peasants. When it came out, the accusation of Misbach was inevitable. Even though they did not directly give orders to the peasants to protest, the organization of the peasants and propaganda efforts toward the protest had considerable influence. So this article, which illustrates the relationship between the action and propaganda of Haji Misbach to the peasant protest in Surakarta, would support the Author's past writing in his thesis At the Department of History Education in the Indonesia University of Education.